Chemical constituents and antioxidant activity of extracts obtained from branch bark of Bursera simaruba - Moustapha BAH (Boletín Latinoamericano y del Caribe de Plantas Medicinales y Aromáticas, 2014)
The chemical constituents of the hexane and methanol extracts obtained from the branch bark of Bursera simaruba (Burseraceae) grown in Querétaro, Mexico, were investigated by GC - MS, HPLC coupled to DAD, and NMR techniques. Seventeen compounds, including terpenoids, flavonoids, pheno lic acids, long-chain fatty acids (FA), methyl esters of FA and sucrose, were identified. In addition, an assessment of the antiradical activity of the methanol extract (ME) was also carried out using DPPH, ABTS, FRAP and DPV assays. The DPPH, ABTS and FRA P assays showed a low antioxidant capacity for the ME. This was in accordance with the relatively low quantities of phenols found in the extract. However, according to the differential pulse voltammetry assay (DVP), this extract exhibited an oxidation pote ntial close to those of quercetin and (+) - catechin, two of the flavonoids with recognized good antioxidant power. This indicated that the ME does contain compounds with good antioxidant capacity and suggested that sometimes the most popular methods commonl y used might be underestimating the true antioxidant capacities of plant samples and how the DPV is a valuable complementary tool to be ta ken into consideration when conducting these in vitro assays.